Peran Flavonoid Sebagai Antiulser dan Antioksidan pada Ulkus Duodenum - Zahra, Aulia Jannatuz; Susianti, Susianti; Happy, Terza Aflika; Soleha, Tri Umiana (Medula, 2024)
Duodenal ulcer is a pathological condition characterized by damage to the duodenal mucosa due to an imbalance between protective and aggressive factors, such as gastric acid and pepsin. The primary factors contributing to the development of this ulcer include Helicobacter pylori infection. Additionally, prolonged use of Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) is also a significant factor in the occurrence of duodenal ulcers, as these drugs inhibit prostaglandin synthesis, which plays a crucial role in mucosal protection. In Indonesia, the prevalence of duodenal ulcers is estimated to be around 11–14%. Flavonoids, as bioactive compounds with antioxidant, anti-inflammatory, and anti-ulcer properties, have been widely studied for their potential in the management of peptic ulcers, including duodenal ulcers. Flavonoids have been shown to inhibit gastric acid secretion, stimulate mucus production, and protect the gastrointestinal mucosa through cytoprotective and antioxidative mechanisms, specifically by inhibiting reactive oxygen species (ROS). Furthermore, flavonoids have the ability to suppress H. pylori growth, thereby contributing to the prevention of ulcer pathogenesis caused by this bacterium. Flavonoids also enhance blood flow to the gastric mucosa and modulate enzymes involved in epithelial defense. Despite these benefits, the main challenges in utilizing flavonoids are their low bioavailability and potential toxicity at high doses. Therefore, further studies are essential to evaluate the efficacy, safety, and formulation optimization of flavonoids to enhance their availability as a natural therapeutic alternative and their application in the clinical treatment of peptic ulcers.